International prevalence of consultation with a naturopathic practitioner: a systematic review and meta-analysis - Amie Steel; Jon Adams; Brenda Leung; Holger Cramer; Matthew J Leach; Jon Wardle; Joshua Goldenberg; Janet Schloss; Rebecca Redmond; Joanna Elizabeth Harnett; Claudine Van de Venter; Andy McLintock; et al. (BMJ Open)
Objectives Naturopathy is a traditional medicine system informed by codified philosophies and principles, and an emphasis on non-pharmacologic therapeutic interventions. While naturopathy is practised by approximately 75 000–100 000 000 naturopathic practitioners in at least 98 countries, little is known about the international prevalence of history of consultation with a naturopathic practitioner. This study reports a systematic review and meta-analysis of studies describing the global prevalence of history of consultation with a naturopathic practitioner by the general population.Setting The included literature was identified through a systematic search of eight databases between September and October 2019, as well as the grey literature.Participants Studies were included if they reported the prevalence rate of consultations with a naturopathic practitioner by the general population.Interventions Survey items needed to report consultations with a naturopathic practitioner as defined in the country where data was collected, and not combine naturopathic consultations with other health services or only report consulations for illness populations.Primary and secondary outcome measures Primary measures used for the analysis was consultations in the previous 12 months. Other prevalence timeframes were reported as secondary measures.Methods Meta-analysis of prevalence data was conducted using random effects models based on individual countries and WHO world regions.Results The literature search identified eight manuscripts summarising 14 studies reporting prevalence for inclusion in the review. All included studies had a low risk of bias. Meta-analysis of the included studies by world region found the 12-month prevalence of history of naturopathy consultations ranged from 1% in the Region of the Americas to 6% in the European and Western Pacific Regions.Conclusions There are up to sixfold differences in the prevalence of naturopathy consults over 12 months between and within world regions, which may be driven by a range of policy, legislative and social factors.PROSPERO registration number CRD42020145529.